The effectiveness of an outpatient Acceptance and Commitment Therapy Group programme for a transdiagnostic population. (12th February 2015) - Pinto, Richelle Anne; Kienhuis, Mandy; Slevison, Monique; Chester, Andrea; Sloss, Annie; Yap, Keong
Abstract: Background: Although a growing number of studies have demonstrated the efficacy of Acceptance and Commitment Therapy (ACT) for the treatment of psychological disorders, the effectiveness of transdiagnostic group ACT programmes in an applied clinical setting requires further evaluation. Methods: The current study examined the effectiveness of a 10‐week ACT transdiagnostic group programme delivered in a private psychiatric hospital. Pre‐ and post‐treatment outcomes were measured in 55 adults presenting with various psychiatric diagnoses. Treatment processes were also analysed. Results: At post‐intervention, participants demonstrated significantly greater valued living, cognitive defusion, and acceptance. No significant differences were evident in participants' mindfulness. Significant improvements were also evident on depression, anxiety, stress, functional disability, satisfaction with life, and personal well‐being. Reliable change indices were also calculated and revealed reliable improvements in a range of outcomes for 27% to 46% of participants. Participant attendance rates, clinician adherence to the manualised ACT content, and patient satisfaction were all high. Conclusions: Collectively, results provided support for the effectiveness of ACT in increasing psychological flexibility and improving psychological symptoms in a transdiagnostic population. However, the current study also showed that many patients did not respond to the intervention and further research is recommended to ascertain predictors of treatment response. Abstract :